PEMERIKSAAN KUALITAS AIR SUNGAI SEI KERA MEDAN DENGAN METODE SPEKTROPHOTOMETRI - Rachmi, Emi; Nugrahalia, Meida; Karim, Abdul (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2016)
Sei Kera river which is located in the district of Medan Perjuangan, Medan, North Sumatra accross the settlements with 10 villages namely Tegal Rejo, Sidorame West I, Waterquality status,Water quality standard, Storet method.Sidorame West II, Sidorame EastI, Sidorame East II, Sei Kera Hilir I, Sei Kera Hilir II, Sei Kera Hulu, Heroes and Pandau Hulu which is occupied 93.328 people. This study uses quantitative analysis is the quality of water in Sei Kerariver from the result of water quality parameters include parameters TotalofSuspended Solidsd (TSS), Chrome 6+, Chlorine, Nitrite, Fluoride, Phosphate, Sulfates, Sulfides, Nitrates, Chemical Oxygen Demand (COD) and Detergents are made in 2 (two) points using purposive sampling method, the area of the river downstream at bridge on Mabar Street (point 1)and upstream bridge Cemara Street (point 2). Sampling is done within 3 (three) perod, and the data which has got is analyzed by spectrophotometry Method with approach criteria quality of water based on PP. 82 of 2001 on the Management of Water Quality and Water Pollution Control, the result is Sei Kera river from point 1 to point 2 can only meet Water Quality Standard Class III that the allocation can be used for fresh water cultivation for fish, animal husbandry, water to irrigate landscaping, and other uses that quality of water similar requirements to these purpioses.